Desamortización y transferencia de propiedad inmobiliaria en la ciudad de León a principios del siglo XIX (Estudios humanísticos. Geografía, historia y arte, 1997)
During the two first decacles of the XIX century and within the Old Regime crisis context, wealty people were offered excellent opportunities to acquire either urban or rural properties.Taking the town of León as the background, this article aims to give the reader an approach to this theme by referring to Godoy's disentailment, to the common lands selling and to the assignment of small prices of land which all took place during the Independance War.